Strategic Clarity and Effect of Organizational Excellence: Analytical Research in The State Company for Automobile and Equipment Industry: An Extracted Research From PhD Dissertation. - DHAHER, MI'AD HAMEED; SAAED, Dr. HADEEL KADHIM (The journal of contemporary issues in business and government, 2021)
The main objective the research is to investigate the relationship link and influence between the strategic clarity and the Organizational Excellence in the General Company for the automotive industry and equipment and to identify the pattern and nature of thinking incumbents administrative in the company concerned in order to determine the appropriate action and that lead to the consolidation approach of clarity and strategic and directing them towards achieving excellence Organizational , data from (1 has collected 76 respondents) represented a sample of managers and data analysis employed statistical programs ( SPSS, AMOS )Through the adoption of appropriate statistical methods .The results showed the health of relationships link and influence on the level of key variables and sub - dimensions, indicating the role of vital strategic clarity to achieve excellence Organizational in the company surveyed.